Geotecnologias aplicadas à compartimentação geomorfológica do município de São Sepé - RS - Rosa, Eloisa Penna da (2019)
The relief results from the action of antagonistic forces synthesized by tectonic and structural activities, and by morphoclimatic mechanisms over geological time, may occur successively or simultaneously. Geomorphological cartography, allied with geotechnologies, allows gathering relief aspects, providing the representation of information to be applied in the planning of the territory. Thus, the present research aims to perform the geomorphological compartmentalization of the municipality of São Sepé, located in the central region of Rio Grande do Sul. The methodology used included the use of Geographic Information Systems for the analysis and manipulation of the data in the definition of geomorphological compartmentalization. The geomorphological compartmentalization of the research is based on the taxonomic levels proposed by Ross (1990, 1992), in relation to the 3rd level (Relief Units), 4th level (Relief Elements) and 5th level (hillside forms). Regarding the results of this research, first an analysis of the elements of the physical environment is presented: hydrography, relief and lithologies. At the third taxonomic level, the relief units were defined: flat areas, gentle hills, rolling hills and the association between hills and earthmounds. For the Relief Elements (4th level), the ten main were established: flat, peak, ridge, step, secondary ridge, hillside, chiselled, base of the hill, valley and gap. In the 5th level the forms of the hillsides are defined in XII units through the geomorphometric units. In the relationship between taxonomic levels, in the relief, units of flat areas predominate the elements of flat areas and the hillsides defined by unit X. In the gentle hills the hillsides, elements of the unit X also prevail. In the rolling hills, the elements of hillsides stand out and the predominant hillsides are of unit I. Finally, in the unit of association of hillsides and earthmounds, predominate the elements of hillsides of the unit III. In general, it is considered satisfactory the application the methodology for relief mapping, utilizated because it was possible to elaborate a representative geomorphological compartmentalization for the study area and which important cartographic products can be used as subsidies to those interested in the area of study.